A Randomized Controlled Pilot Trial About the Influence of Kyusho Jitsu Exercise on Self-efficacy, Fear, Depression, and Distress of Breast Cancer Patients within Follow-up Care. (September 2021) - Salchow, Jannike L; Strunk, Maximilian A; Niels, Timo; Steck, Jule; Minto, Carrie-Ann; Baumann, Freerk T
Introduction: Breast cancer survivors are faced with several psychological issues. We report the influence on self-efficacy by a holistic orientated training schedule based on the "Kyusho Jitsu" martial art and explore the effects on self-efficacy, distress, fear, and depression. Methods: Breast cancer survivors (N = 51) were randomly assigned to an intervention (n = 30) or control group (n = 21). The intervention group participated in a Kyusho Jitsu intervention twice a week over a period of 6 months, the control group received no intervention. Patients from both groups were measured at baseline, 3 and 6 months on level of self-efficacy (German General-Self-Efficacy Scale, SWE), stress (Perceived Stress Questionnaire, PSQ20), and fear and depression (Hospital Anxiety and Depression Scale, HADS). Results: Analysis of the original data showed a significant difference between both groups regarding the subscale "joy" ( P  = .018). Several significant results within the intervention group were seen in self-efficacy ( P  = .014), fear ( P  = .009) and the overall score for fear and depression ( P  = .043). Both groups improved significantly within "worries" (intervention P  = .006, control P  = .019) and the PSQ20 overall score (both P  = .005). The control group also significantly improved in the subscale for "demands" ( P  = .019). Conclusion: To summarize, our pilot study showed that Kyusho Jitsu training is safe and feasible. Though, the intervention alone cannot be considered as being effective enough to help breast cancer survivors regarding relevant psychological issues, but might be an important supplement offer within follow-up care.